Legal Aspec Bioprospecting Conservation of Medicinal Plants in Indonesia - Hafid Zakariya1 , Pramono Hadi2 , Nur Rohim Yunus3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The country of Indonesia is an archipelago, which has various types of plants. One of them is a medicinal plant. This plant has ingredients that can be used as a treatment. But by seeing the high population growth of Indonesia, the medicinal plants are threatened. This makes the need for an action that can maintain the existence of these medicinal plants. Bioprospection conservation is an effort to preserve and develop medicinal plants so that their presence is not lost.